Eighth International Conference on Vibration Measurements by Laser Techniques: Advances and Applications 2008
DOI: 10.1117/12.803157
|View full text |Cite
|
Sign up to set email alerts
|

Retardation effects in laser-Doppler measurements

Abstract: Although the Doppler-effect is well known, some recent publications discuss the necessity of relativistic corrections in the measurements of two-beam interferometers. This is remarkable because sensor and detector are in the same reference frame and, therefore, it is not necessary to employ the Lorentz transformation. The whole consideration can be made in one inertial frame even if one reflector is moving in respect to the frame of source and detector. However, the commonly used equation for the Doppler-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One can use a relativistic approach, which takes into account a transformation of space and time coordinates, as explained in [1]. However, recent studies on retardation effects in laser Doppler measurements [2] demonstrated that it is not necessary to consider relativistic effects in measurements of a two-beam interferometer, since the source and the observer are in the same reference frame. This condition is the one depicted in Fig.…”
Section: Ael Accessible Emission Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…One can use a relativistic approach, which takes into account a transformation of space and time coordinates, as explained in [1]. However, recent studies on retardation effects in laser Doppler measurements [2] demonstrated that it is not necessary to consider relativistic effects in measurements of a two-beam interferometer, since the source and the observer are in the same reference frame. This condition is the one depicted in Fig.…”
Section: Ael Accessible Emission Limitsmentioning
confidence: 99%
“…This holding, when the velocity is much less than the speed of light (v < < c), which is almost always the case in standard applications, it might be possible to expand in a power series in v/c and stop the expansion to the first order, so to obtain the Doppler shift ( f ) as shown below in Eq. (2). The equivalence c = fλ and the prosthaphaeresis formulas were utilized to obtain the well-known expression for the Doppler shift.…”
Section: Ael Accessible Emission Limitsmentioning
confidence: 99%